Electronic Part and Automobile Manufacturer's Knowledge Management Practices towards Electric Vehicle Industry's Business Expansion in Thailand - treewichit, worathep; Sritong, Charcrit; Siriwoharn, Theathanick (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2022)
The objectives of this research were to study the problems of knowledge management practices of electrical components manufacturer electronics and automotive towards the business expansion in the electric automotive industry in Thailand, and to propose the guidelines for knowledge management practices of electrical components manufacturer electronics and automotive in order to expand the business in the electric automotive industry in Thailand. The researcher used a qualitative research methods, which was a specific case study and a personal in-depth interviews for 5 people, and the academic experts/the experience and expertise experts in the production of electrical components electronics and automotive for 3 people. This research used the semi-structured interview technique to be a tool in order to collect the data as well as the content analysis by using the triangulation method to validate data. The results revealed that the problems of knowledge management practices of electrical components manufacturer electronics and automotive consisted of knowledge creation and acquisition aspect, knowledge repository system aspect, knowledge sharing aspect and knowledge integration aspect. Moreover, these 4 aspects had an impact towards business expansion in the electric automotive industry in Thailand. In addition, the guidelines for knowledge management practices of electrical components manufacturer electronics and automotive in order to expand the business in the electric automotive industry in Thailand found that the manufacturers need to have a good perception on knowledge creation and acquisition aspect. The standardization of knowledge repository system aspect is concerned to be used for management and employee level in terms of knowledge sharing practices as well as the knowledge integration aspect should be applied for efficiency and effectiveness among employees. This research can be the guidelines to develop and improve the knowledge management practices in reverent industries in order to strengthen to achieve the industries’ goal setting plan in the future.